Sarcoglycanopathy - a rare case report and literature review - Mustafa, Ekramul; Khandaker, Md Azizul Hasan; Rashid, Md Mamunur; Ghose, Swapon Kumar; Salehin, Masood; Hussain, Ahmed Riyad; Sabah, KM Nurus (Journal of Dhaka Medical College, 2015)
Sarcoglycanopathies are relatively rare progressive muscular dystrophies with autosomal recessive inheritance designated as á, â, ã, or ä sarcoglycanopath.; which belong to the group of limb girdle muscular dystrophies and are caused by mutations in any of the four sarcoglycan genes: alpha (LGMD 2D), beta (LGMD 2E), gamma (LGMD 2C) and delta (LGMD 2F). The phenotype resembles dystrophinopathies due to proximal muscle weakness and calf hypertrophy. Reports from Bangladesh are scarce. We report a rare case of primary sarcoglycanopathy (SGP) which emphasizes the evolving concept of dystrophinopathy to sarco-glycanopathy. and describe literature pertaining to this rare entity DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21551 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 232-235